Molecular genetic predictors of progression of triple negative breast cancer - I. S. Panchenko; V. V. Rodionov; V. V. Kometova; S. V. Panchenko; M. G. Sharafutdinov; I. A. Lavrentieva (Сибирский онкологический журнал)
Introduction. Triple-negative breast cancer (TNBC) is a group of malignant breast tumors with poor prognosis and varying molecular genetic characteristics. In TNBC, genes determine whether patients belong to clusters that differ in prognosis. There are not enough studies that consider genes as risk factors for progression. The aim of this study was to identify genes of TNBC which are associated with high risk progression, and evaluate their prognostic significance. Material and methods. This study included 246 patients with TNBC. Forty-five genes performing various functions were used as a panel of genes. The molecular genetic research technique consisted of preliminary RNA isolation followed by real-time cDNA amplification using PCR. Mean gene expression levels were calculated as measures of central tendency of the numerical value with 95 CI. The significance of the influence of genes on the risk of progression (locoregional recurrence or distant metastasis) was assessed using the formation of the linear discriminant function and construction of ROC curve. The relationship between genes and clinical and morphological parameters was assessed using correlation analysis (Pearson’s χ2 Spearman’s ρ test). After determining the threshold values of gene expression levels and subsequent ranking of patients into groups with high and low levels, an analysis of the survival of the formed groups was carried out (Kaplan-Meier curves). When comparing survival curves, the long-rank test was used. Results. Two genes: PGR (p=0.007) and AR (p=0.001), which were associated with locoregional relapse, and 1 gene: FOXA1, which was associated with distant metastasis (p=0.001), were selected using discriminant analysis. Statistically significant (p<0.05) correlations between the gene expressions and the tumor grade and the level of proliferative activity (Ki67) were found. Low expression levels of PGR (≤-6.4), AR (≤-4.7), FOXA1 (≤-4.4) were associated with improved overall survival. Conclusion. In patients with TNBC, PGR and AR are markers of locoregional relapse, and FOXA1 is a marker of distant metastasis. The expression of PGR, AR, FOXA1 was significantly correlated with the grade of the tumor and Ki67. Low gene expressions were associated with favorable prognosis.